2017
DOI: 10.2337/dc17-1351
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Predictive Capability of a 1-Hour Oral Glucose Tolerance Test: A Prospective Population-Based Cohort Study

Abstract: OBJECTIVETo examine whether the 1-h blood glucose measurement would be a more suitable screening tool for assessing the risk of diabetes and its complications than the 2-h measurement. RESEARCH DESIGN AND METHODSWe conducted a prospective population-based cohort study of 4,867 men, randomly selected from prespecified birth cohorts between 1921 and 1949, who underwent an oral glucose tolerance test with blood glucose measurements at 0, 1, and 2 h. Subjects were followed for up to 39 years, with registry-based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
90
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 44 publications
3
90
0
2
Order By: Relevance
“…Thereafter, elevated 1hPG has been consistently reported to be associated with impaired insulin sensitivity, reduced β‐cell function and a less favourable cardiometabolic risk profile . Furthermore, the predictive power of 1hPG has been confirmed in large cohorts of adults from different ethnic populations …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thereafter, elevated 1hPG has been consistently reported to be associated with impaired insulin sensitivity, reduced β‐cell function and a less favourable cardiometabolic risk profile . Furthermore, the predictive power of 1hPG has been confirmed in large cohorts of adults from different ethnic populations …”
Section: Introductionmentioning
confidence: 90%
“…In adults, several longitudinal studies have recently identified 1‐hour post‐load glucose concentration (1hPG) during an oral glucose tolerance test (OGTT) as an earlier and more accurate predictor of diabetes than currently used biomarkers . In 2007, Abdul‐Ghani et al found that the area under the ROC curve for 1hPG to predict future diabetes is significantly greater than that of fasting and 2‐hour plasma glucose.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported impaired β‐cell secretory capacity even in the setting of PI‐CF and normal glucose tolerance (NGT), defined using the 1‐hour OGTT glucose <200 mg/dL, compared to pancreatic sufficient CF (PS‐CF) and healthy control subjects . In non‐CF populations, 1‐hour OGTT glucose above a threshold as low as 155 mg/dL (8.6 mmol/L) portends increased risk of developing type 2 diabetes, greater adverse cardiovascular disease outcomes, and increased mortality, and is associated with impaired β‐cell function . In CF, higher 1‐hour glucose is associated with a 4‐to‐5‐fold increased risk for developing CFRD over the subsequent 5 years .…”
Section: Introductionmentioning
confidence: 99%
“…In a 33 year study, it was not only a better predictor of incident diabetes, but also of diabetes complications and mortality [4]. Robust evidence from the Botnia study and Malmö Prevention Project cohorts supports 1hPG as the best simple variable predicting incident type 2 diabetes, in comparison with other indices [1].…”
mentioning
confidence: 99%